2022
DOI: 10.12998/wjcc.v10.i21.7209
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and small intestinal bacterial overgrowth–more than what meets the eye

Abstract: Helicobacter pylori ( H. pylori ) infection is very common and affects a significant proportion of the world population. In contrast, the prevalence of small intestinal bacterial overgrowth (SIBO) in the general population is not well understood. There can be coexistence of both disease states in a given patient and their clinical symptoms may also overlap with one and another. There is no clear clinical guidelines for testing for and treating SIBO in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Conversely, only 21.9% patients without H. pylori infection met the criteria for SIBO [ 103 ]. These data suggested that the incidence of SIBO was twice as high in patients infected with H. pylori compared to those uninfected patient [ 105 ]. This conclusion was further supported by a separate study conducted in 2018, which reported that 53% patients with concurrent H. pylori infection and SIBO were identified [ 106 ].…”
Section: H Pylori Infection In Pd Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, only 21.9% patients without H. pylori infection met the criteria for SIBO [ 103 ]. These data suggested that the incidence of SIBO was twice as high in patients infected with H. pylori compared to those uninfected patient [ 105 ]. This conclusion was further supported by a separate study conducted in 2018, which reported that 53% patients with concurrent H. pylori infection and SIBO were identified [ 106 ].…”
Section: H Pylori Infection In Pd Pathogenesismentioning
confidence: 99%
“…It is noteworthy that H. pylori infection causes mitochondria impairment, and the coexistence of H. pylori and damaged mitochondria synergistically contribute to the progression of SIBO [ 107 , 105 ] (Fig. 1 C).…”
Section: H Pylori Infection In Pd Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation